1997
DOI: 10.1002/(sici)1097-0169(1997)38:4<397::aid-cm9>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for several roles of dynein in pigment transport in melanophores

Abstract: Melanophores are specialized cells that transport pigment granules to and from the cell center, giving animals the ability to change skin color. A kinesin‐related plus‐end motor has previously been shown to be responsible for pigment granule dispersion [V.I. Rodionov, F.K. Gyoeva, and V.I. Gelfand. Proc. Natl. Acad. Sci. USA. 1991, 88:4956‐4960]. Here, we have microinjected a dynein antibody (70.1) into cultured cod (Gadus morhua) melanophores and used the dynein inhibitor vanadate on permeabilized melanophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
62
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 39 publications
(43 reference statements)
5
62
2
Order By: Relevance
“…By exploiting this property, biologists have used melanosomes as markers for in vivo organelle transport studies (1). Several groups (2)(3)(4) have shown that myosin V, cytoplasmic dynein, and kinesin-2 are the molecular motors in charge of melanosome transport in Xenopus melanophores. Among these molecular motors, heterotrimeric kinesin-2, which contains two different polypeptide chains with motor domains, Xklp3A and Xklp3B, has been shown to be responsible for the dispersion of melanosomes (3).…”
mentioning
confidence: 99%
“…By exploiting this property, biologists have used melanosomes as markers for in vivo organelle transport studies (1). Several groups (2)(3)(4) have shown that myosin V, cytoplasmic dynein, and kinesin-2 are the molecular motors in charge of melanosome transport in Xenopus melanophores. Among these molecular motors, heterotrimeric kinesin-2, which contains two different polypeptide chains with motor domains, Xklp3A and Xklp3B, has been shown to be responsible for the dispersion of melanosomes (3).…”
mentioning
confidence: 99%
“…The skin explants were then fixed in ice-cold methanol for 6 minutes and rinsed in phosphate buffered saline for subsequent scoring of the amount of deformed versus spherical CMP´s on each explant. The results showed that microtubules, but not actin (not shown), maintain the spherical shape of the CPM (Nilsson and Wallin, 1997). Also here, the non-cell membrane permeable agent vanadate was added at different concentrations, now together with norepinephrine in the saponin containing lysis buffer.…”
mentioning
confidence: 87%
“…Skin explants in cultures have successfully been used for treatments with non-cell permeable agents to investigate intracellular mechanisms behind maintenance of the circular central pigment mass (CPM) and melanosome movements (Nilsson and Wallin 1997). The culture procedure makes the melanophores more exposed to the agents compared to the original biopsy, and the colour change reaction therefore occurs much faster.…”
mentioning
confidence: 99%
“…The pigment cells respond to brightness, ultraviolet light, pressure, temperature, fish activity, pH, and chemicals via the neurohumoural and neurochemical systems producing melanophore-stimulating hormone, adrenocorticotrophic hormone, prolactin, somatolactin, melanin-concentrating hormone, melatonin, epinephrine and norepinephrine. 17,[19][20][21] In vertebrates, pigment cells develop from the neural crest of the embryo 22,23 . In the epidermis and dermis there are four pigment types: iridescent or blue, black, red, and yellow, which are made up of, respectively, blue and green pigment-containing iridocytes and guanophores, melanophores, erythrophores, and xanthophores.…”
Section: Pigments and Body Coloursmentioning
confidence: 99%